Metabolic diversification of cells during the development of yeast colonies - Váchová, Libuse; Kucerová, Helena; Devaux, Frederic; Ulehlová, Miroslava; Palková, Zdena (Environmental microbiology, 2009)
Microorganisms in nature form organized multicellular structures (colonies, biofilms) possessing properties absent in individual cells. These are often related to the better ability of communities to survive long-lasting starvation and stress and include mechanisms of adaptation and cell specialization. Thus, yeast colonies pass through distinct developmental phases characterized by changes in pH and the production of ammonia-signalling molecules. Here, we show that Saccharomyces cerevisiae colony transition between major developmental phases (first acidic, alkali, second acidic) is accompanied by striking transcription changes, while the development within each particular phase is guided mostly at the post-transcriptional level. First- and second-acidic-phase colonies markedly differ. Second-acidic-phase colonies maintain the adaptive metabolism activated in the ammonia-producing period, supplemented by additional changes, which begin after colonies enter the second acidic phase. Cells with particular properties are not homogenously dispersed throughout the colony population, but localize to specific colony regions. Thus, cells located at the colony margin are able to export higher amounts of ammonium than central cells and to activate an adaptive metabolism. In contrast, central chronologically aged cells are unable to undergo these changes but they maintain higher levels of various stress-defence enzymes. These divergent properties of both cell types determine their consequent dissimilar fate.
Keywords: Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; Adaptation, Physiological; Gene Expression Regulation, Fungal; Saccharomyces cerevisiae Proteins; regulace genové exprese u hub; Culture Media; lidé; Ammonia; fyziologická adaptace; amoniak; kultivační média; Humans